PERKEMBANGAN INDUSTRI PENGOLAHAN DI KOTA BANJARMASIN - GHIYATS MARAYA RIZKI (PPJP Universitas Lambung Mangkurat, 2018)
Ghiyats Maraya Rizki (2017) Development of Processing Industry In Banjarmasin City. Advisor: Dr. Hj. Ika Chandriyanti M.P.This study aims to examine the factors that affect the economic growth of the processing industry sector in the city of Banjarmasin. Independent variables in this research are Number of Business Unit of Processing Industry, Processing Industry Investment, and Processing Industry Worker, dependennya is economic growth of processing industry sector in Banjarmasin City.The data analyzed in this study is time series data obtained from the Central Bureau of Statistics Banjarmasin. Data analysis technique used is regression analysis by using semi log. Prior to the analysis, first classic assumption test to detect multikolineritas, heteroskedastisitas and autocorrelation.Research shows that only variable of business unit partially influence to economic growth of processing industry sector in Banjarmasin City. Together the variables of business unit, investment, and labor have influence to economic growth of processing industry sector in Banjarmasin City. Keywords: Economic Growth of Industrial Sector of Processing, Number of Business Unit of Processing Industry, Investment of Processing Industry, and Manpower of Processing Industry, Banjarmasin City.